Thorium-232 protoni-indusoidun fission tuottojakauma - Korkiamäki, Rami (2024)
In this thesis we studied how the fission yields of thorium-232 proton-induced fission vary with different elements depending on how the fission products are mass separated and which method is used to determine the fission yields. Measurements were done using gamma spectroscopy, multi-reflection time-of-flight mass separator (MR-TOF) and JYFLTRAP Penning's trap for mass numbers of A=80, 86, 100, 104, 110, 124, 136. The relative fission yields given by the methods were compared within each of the measured mass number. Additionally, MR-TOF was used to determine the relative independent isotopic fission yield distributions for niobium, molybdenum, technetium, ruthenium, rhodium and palladium for mass numbers A=103-112. These distributions were compared to previously measured fission yields obtained using JYFLTRAP. No significant impact was found between the different methods when examining the relative fission yields. The differences between the methods mostly fall within the reliability margins. An exception to this are $^{80}$As and $^{136}$Te, whose measured yields appear to be significantly lower when measured with MR-TOF and JYFLTRAP. No particular large differences were observed between the relative independent isotopic fission yields of MR-TOF and JYFLTRAP.